2021
DOI: 10.1093/mnras/stab2903
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the X-ray spectral curvature of Mkn 421 using broad-band AstroSat observations

Abstract: We present a time-resolved X-ray spectral study of the high energy peaked blazar Mkn 421 using simultaneous broadband observations from the LAXPC and SXT instruments on-board AstroSat. The ∼400 ksec long observation taken during 3–8 January, 2017 was divided into segments of 10 ksecs. Each segment was fitted using synchrotron emission from particles whose energy distribution was represented by a log-parabola model. We also considered particle energy distribution models where (i) the radiative cooling leads to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 73 publications
2
10
0
Order By: Relevance
“…In §3, we present the spectral study using log-parabola model ( §3.1), Power-law with maximum electron energy model ( §3.2), and Energy dependent model ( §3.3); EDD ( §3.3.1) and EDA ( §3.3.2). In §3.4, we compare the correlation study results with the ones obtained with short-term flare in (Hota et al 2021). Finally, we discuss and conclude the results in §4.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…In §3, we present the spectral study using log-parabola model ( §3.1), Power-law with maximum electron energy model ( §3.2), and Energy dependent model ( §3.3); EDD ( §3.3.1) and EDA ( §3.3.2). In §3.4, we compare the correlation study results with the ones obtained with short-term flare in (Hota et al 2021). Finally, we discuss and conclude the results in §4.…”
Section: Introductionmentioning
confidence: 74%
“…Furthermore, Goswami et al 2020 showed that the power-law with γmax model can explain the curved spectrum in the X-ray band in case of EHBL source RGB J0710+591, where the synchrotron spectrum corresponding to the decline of the particle number density near the maximum available electron energy, can explain the sharp spectral curvature. Nevertheless, Hota et al 2021 had shown with the approach of spectral parameter correlations that the obtained correlations are not consistent with the predictions from the power-law with γmax model. Instead, they showed that curved spectrum can be interpreted as an outcome of energy dependent acceleration and diffusion of the particles.…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations